Efek subletal campuran ekstrak daun srikaya (Annona squamosa L.) dan rimpang kunyit (Curcuma domestica Val.) terhadap larva Spodoptera litura F. - Ramadhan Taufika; Siti Sumarmi; Setyo Andi Nugroho (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Spodoptera litura (Lepidoptera: Noctuidae) larvae are polyphagous insects whose populations cause damage to various types of plantations, horticulture, and food so that control efforts need to be done. One way to control the environment of environmentally friendly S. litura larvae is to use a plant-based insecticide, a mixture of A. squamosa leaf extract and C. domestica rhizome (test extract appendix). The purpose of this study was to determine the subletal effect of the test extract mixture on S. litura larvae, namely the duration of larvae and pupae stage, pupae weight, morphology and imago viability, and the ability of female imago to lay eggs to produce offspring. The test was carried out by the method of feed dip into the test extract mixture. Data on pupae weight were analyzed with ANOVA, followed by Duncan's further test with a 5% confidence level using SPSS 21 program. The results showed that the test extract mixture extended the stages of larvae and pupae, reduced pupa weight, imago wings did not develop fully, reduced imago size, and did not imago able to produce eggs. The results of this study could then be further tested on a greenhouse scale and photochemical analysis of a test extract mixture to determine bioactive compounds that act as plant-based insecticides.